Codigestion of food waste and real traditional Chinese medicine wastewater in anaerobic membrane bioreactor: Stability mechanism and microbial community dynamics - Yong-Xin Cui; Bao-Shan Xing; Su Li; Zi-Yi Wang; Xiaochang C. Wang; Yu-You Li; Rong Chen (Water Research, 2026)

Origin and evolution of granites in the world-class Gejiu Sn-Cu-polymetallic ore district: Implications for mineralization and tectonic setting - Guangjie Li; Yongqing Chen; Xu Zhu; Rong Yang (Journal of Geochemical Exploration, 2026)

Effects of equivalence ratio on vented H2/CH4/air explosions in the chamber with a hinged vent panel - Hongzhe Rong; Jialin Li; Jin Guo; Yiming Wang; Zhongrui Chen; Fuqiang Yang (Fuel, 2026)

Regulating the d-band center of Ru/CoMoO4 ternary heterostructure by interface engineering for accelerated hydrogen adsorption kinetics - Miao Ma; Min Yang; Cai-Yue Zhang; Hai-Yi Sun; Rong-Jing Su; Xiao-Rui Yue; Chen-Xi Li; Yong-Ming Chai; Bin Dong (Fuel, 2026)

Magnetic biochar as dual-functional mediator for low-field magnetic separation of vivianite and membrane fouling mitigation in anaerobic membrane bioreactors - Feng-Ai Yang; Ying Dong; Jifei Chang; Rong Chen; Xin Wang; Juncheng Liu; Fernanda Leite Lobo; Devard I. Stom; Nan Li (Bioresource Technology, 2026)

Biochar-assisted rapid formation of core–biofilm anammox granules via interfacial trapping of extracellular polymeric substances - Jingwei Fu; Yue Li; Yaqian Liu; Can Xiong; Pei Li; Xuanqi Long; Qian Li; Rong Chen (Bioresource Technology, 2026)

Correction to: Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

MiR-4327 targets TP53 to promote cervical cancer cell proliferation - Mei-Lin Chen; Chen-Yang Chu; Feng-Xian Zhang; Li-Pei Zhang; Ying Yang; Bai-Zhao Peng; Chuang-Hai Wu; Xiao-Mei Chen; Yan-Ting You; Bing-Ying Rong; Hiu Yee Kwan; Xiao-Shan Zhao; et al. (Functional & Integrative Genomics, 2026)
Cervical cancer is a leading cause of female malignancy worldwide. While microRNA-4327 (miR-4327) has been implicated as a potential oncogene, its functional role and molecular mechanisms in cervical cancer pathogenesis remain unclear. This study aimed to determine the oncogenic function of miR-4327 and elucidate its downstream regulatory mechanism in cervical cancer pathogenesis. We measured miR-4327 expression in clinical cervical cancer tissues and cell lines using quantitative real-time PCR (qRT-PCR). We then assessed its effects on proliferation, migration, invasion, and cell cycle progression through functional assays including cell counting kit-8 (CCK-8), colony formation, transwell, and flow cytometry. To evaluate tumor growth in vivo, we established a xenograft model in non-obese diabetic (NOD)-severe combined immune-deficient (scid) mice. Using bioinformatic analysis and luciferase reporter assays, we identified TP53 as a direct target of miR-4327 and further validated this regulatory relationship with gain- and loss-of-function experiments. We found that miR-4327 was significantly upregulated in cervical cancer and promoted malignant phenotypes such as proliferation, migration, invasion, and cell cycle progression in vitro. Consistent with this, overexpression of miR-4327 accelerated tumor growth in vivo. Mechanistically, we confirmed TP53 as a direct functional target of miR-4327. Knocking down TP53 phenocopied the oncogenic effects of miR-4327, while restoring TP53 expression rescued the tumor-promoting effects mediated by miR-4327. These findings reveal a novel miR-4327/TP53 regulatory axis and nominate miR-4327 as a potential therapeutic target for intervention.

Three-dimensional settling map for intelligent detection of activated sludge (AS) properties and health evaluation of AS based wastewater treatment - Jie Lei; Zhe Liu; Guoning Huang; Jiaxuan Wang; Rushuo Yang; Ying Du; Tianyu Han; Zhuangzhuang Yang; Ang Li; Yongjun Liu; Zhenmin Luo; Rong Chen (Water Research, 2026)

Systematic identification pepper CaE2F transcription factor reveals the role of CaDPb in drought stress response - Rong Lu; Yishui Chen; Longxue Li; Zilin Zhang; Qinghong Zhou; Meixia Wang; Huibin Han (Plant Science, 2026)

Artemselenolides I–N, sesquiterpenoid trimers from Artemisia selengensis with antihepatoma activity – structural elucidation, molecular docking and dynamics studies - Rong-Kai Chen; Tian-Ze Li; Yong-Cui Wang; Yun-Bao Ma; Ji-Jun Chen (Phytochemistry, 2026)

Leaching of scandium from a basalt weathering crust-type scandium deposit: An alkali-acid combined treatment method - Xiaorui Wang; Ruidong Yang; Wei Cheng; Rong Chen; Jun Chen; Xinzheng Li (Minerals Engineering, 2026)

High-speed air circulation preserves curcumin bioactivity and enables pH-dependent intestinal release in oyster-based functional foods for IBD dietary intervention - Shuang Gao; Xue Jiang; Yi Rong; Huanhuan Chi; Ci Song; Shujia Wang; Ying Li; Jingjing Chen; Lida Yang; Huawei Ma (Food Research International, 2026)

Temperature-influenced deformation analysis of a full-scale steel-concrete-steel cable support tower model during construction - Zhi-Li Qi; Wei-Le Chen; Jian Li; Jian-Sheng Fan; Rong Xian; Fei Tian; Yu-Fei Liu (Engineering Structures, 2026)

Microalgae-based bioremediation of reverse osmosis concentrate (ROC): Mechanisms, techno-economic bottlenecks, and circular bioeconomy perspectives - Na-Hui Hao; Jun Li; Ya-Rong Qi; Zhuo Chen; Yu-Ming Wang; Yu-Jia Gao; Xu-Cheng Cai; Yu Hong; Hong-Ying Hu; Yin-Hu Wu (Desalination, 2026)

Synergistic room-temperature NH3 sensing: TiO2/g-C3N4 heterojunction with UV-enhanced performance for food freshness monitoring - Haineng Bai; Chenjie Wang; Yang Yu; Yiru Chen; Cheng Feng; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Sihua Zhou; Fuqiang Guo; Qingfeng Li; et al. (Chemical Engineering Journal, 2026)

Orders-of-magnitude reactivity enhancement in persulfate activation by curvature-dependent oxygenated carbon nanotubes - Xin Yang; Zhongyuan Guo; Pufan Wang; Justin Prabowo; Yangyang Wang; Jiaxiang Chen; Jiacheng Wu; Xinyi Huang; Yichen Feng; Chengli Rong; Fangzhou Liu; Hao Li; et al. (Chemical Engineering Journal, 2026)

Biochar promotes methane production from anaerobic digestion: Pore structure regulation and quantitative correlation assessment - Ze-Mu Li; Ai-Hua Li; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Differential stability and adaptive recovery of two-stage partial nitritation–anammox system treating pilot-scale food waste-derived anaerobic membrane bioreactor permeate - Xifang Tang; Shuangquan Zhao; Yihang Li; Yaqian Liu; Hongzhi Chen; Qian Li; Rong Chen (Bioresource Technology, 2026)

Carbon cloth-mediated direct interspecies electron transfer effect on the intensification mechanism of high-load codigestion dynamic membrane bioreactors - Bao-Shan Xing; Yi-Fan Wu; Yi Zhang; Xiaochang C. Wang; Yu-You Li; Rong Chen (Water Research, 2026)

Multi-copy expression of classical swine fever virus E2 in a recombinant pseudorabies virus enhances immunogenicity and supports its potential as a PRV-CSFV bivalent vaccine candidate - Xianfei Shang; Hui Zhao; Yufeng He; Zhenxiang Rong; Xiquan Ke; Jinglei Gao; Ke Zhang; Jiyuan Luo; Min Zhang; Huanchun Chen; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2026)

DNA methylome analysis reveals EjABCG23-mediated epigenetic regulation underlying fruit russeting in white-fleshed loquat - Kun Zhang; Yuying Ding; Rong Su; Chang Liu; Xuelian Li; Yang Wang; Yan Deng; Qiong Zhou; Xiaojun Chen; Yuxing Li; Qunxian Deng (Postharvest Biology and Technology, 2026)

Katian (Late Ordovician) bellerophontoids (Gastropoda) from the shallow-water carbonate succession of Qilian, Northwest China - Wen-Jie Li; Jia-Qi Song; Xin Wei; Yu-Chen Zhang; Rong-Chang Wu; Yong Wang; Peng Tang; Yi Wang; Ren-Bin Zhan (Palaeoworld, 2026)

A highly accurate framework for estimating eye muscle area and backfat thickness of pigs in vivo using deep learning - Yongpeng Li; Yihao Liu; Rong Xu; Chenggan Li; Xian Tong; Liping Pan; Ziyun Liang; Qingshuang Zhou; Yaosheng Chen; Xiaohong Liu; Delin Mo (Meat Science, 2026)

Molecular insights into the transformation of dissolved organic matter from refinery wastewater in receiving water: Photochemical and photo-microbial effects - Leqi Wang; Lei He; Zhuoyu Li; Haifeng Rong; Yifei Zhu; Zelin Niu; Chunmao Chen; Qinghong Wang (Journal of Environmental Chemical Engineering, 2026)

Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

Hydroclimate variability in Northeast China during Marine Isotope Stages 3-2 - Niankang Chen; Ting Xu; Shurun Li; Zeyuan Weng; Zhuoqun Rong; Dongmei Jie; Guizai Gao; Junyi Ge (Global and Planetary Change, 2026)

Immunomodulatory effects of sea buckthorn leaf green tea in cyclophosphamide-induced immunosuppressed mice - Xuhui Kan; Yingjia Yao; Zengshan Chen; Haihong Wang; Chao Che; Quanjin Rong; Fengfeng Du; Jixiang Liu; Xixi Li; Xiaojing Liu; Dongrui Yao (Food Research International, 2026)

Reliable quantification and efficient purification of osteopontin from bovine milk using anion-exchange and membrane chromatography - Xinru Zuo; Shuai Ren; Jinrui Du; Yimeng Li; Muran Ma; Lu Tao; Yinzi Cui; Rong Fan; Yuhong Mao; Guoqiang Chen; Caiyun Wang; Yinhua Wan; et al. (Food Chemistry, 2026)

Flexural bandgap of a metaplate carrying zigzag beam-mass systems - Jung-San Chen; Jie-Sheng Zheng; Yi-Chen Wu; Song-Rong Lin; Wei-Chang Li; Bhisham Sharma; Chin-Han Yang; Yu-Kai Lin (Engineering Structures, 2026)

Synergistic organic–inorganic hybrid interlayer enables tunable Zn2+ desolvation and nucleation toward dendrite-free zinc metal anodes - Xiangzhong Kong; Zicong Wang; Weijia Lv; Yuyang Ding; Xi Chen; Zhongmin Wan; Shi Li; Liya Rong (Chemical Engineering Journal, 2026)

Autogenous dentin graft material promotes bone regeneration involving OPN/CD44-mediated BMSC recruitment - Xin Deng; Jianmin Zhuo; Yanyan Yang; Ziliang Zhou; Jing Li; Rong Rong; Weihong Chen; Jiashen Chen; Siwen Yu; Siyuan Chen; Lu He; Janak Lal Pathak; et al. (Chemical Engineering Journal, 2026)

Advanced nitrogen removal system coupling partial nitritation, anammox, denitrification and oxygen-permeable hollow-fibre membranes for precise oxygen regulation - Xifang Tang; Bao-Shan Xing; Yong-Ning Feng; Liguo Wan; Ling-Hu Li; Xin-Xin Sun; Xiaochang C. Wang; Rong Chen; Yu-You Li (Bioresource Technology, 2026)

Unveiling dynamic membrane functions in a high-rate anaerobic mesophilic co-digestion system treating cow manure and food waste: Performance, digestate characteristics, and microbial community - Hao-Cheng Zhang; Liguo Wan; Yule Han; Xiaochang C. Wang; Rong Chen; Yu-You Li; Bao-Shan Xing (Bioresource Technology, 2026)

Semiconducting polymer-based ratiometric fluorescent nanoprobe for highly accurate imaging of H2S in inflammatory and tumor cells - Chen Han; Xing Wang; Yating He; Rong Wang; Hong-Min Meng; Lin Zhang; Zhaohui Li (Analytica Chimica Acta, 2026)

Enzymatic Preparation of Ejiao (Colla Corii Asini) Peptides and Their Preliminary Mechanism of Melanogenesis Inhibition - Xichao Fu; Shangwei Guo; Meijin Li; Zhijie Chen; Dan Liu; Cuicui Men; Na Yang; Xiaobo Duan; Xiaolu Tang; Yaru Zhang; Haibin Liu; Minghao Liu; et al. (International Journal of Peptide Research and Therapeutics, 2026)

Plant litter enhances hexabromocyclododecane removal in riparian zones at high water level: Insights from the coupling of microbial dehalogenation and carbon cycling - Rong Wang; Juan Chen; Li Wang; Han Gao; Qihao Nie; Shunqing Zhang; Qiming He (Water Research, 2026)

Does the mobility-as-a-service platform alleviate traffic congestion in China? - Zhao Liu; Rong Song; Bin Su; Chen Li (Transportation Research Part D: Transport and Environment, 2026)

Effect of dissolved organic matter chemical characters on microbial community of paddy soils in subtropical China - Yaxin Liu; Yingcong Ye; Daming Li; Rong Cui; Xiaoli Liu; Ling Chen; Meng Wu; Jia Liu; Xi Guo; Ming Liu (Soil and Tillage Research, 2026)

Exogenous dust-induced snow albedo reduction and radiative forcing over the Third Pole - Liang Li; Keqin Duan; Ting Yang; Yuhan Qi; Rong Chen; Peihong Shi (Journal of Hydrology, 2026)

Role of macrophage NLRP3 inflammasome activation in real-ambient particulate matter-induced abnormal hepatic glucose metabolism - Dong Wu; Zhen Zhang; Sixin Chen; Haoran Chen; Daochuan Li; Shuxin Zhang; Junjie Dou; Yuanyuan Ma; Rong Zhang; Lianhua Cui (Journal of Environmental Sciences, 2026)

Engineering bimetallic Cobalt–Iron glycerate Co-Catalysts on bismuth vanadate for improved charge transfer and photoelectrochemical catalytic water oxidation - Tsung-Rong Kuo; He-Jin Li; Kai-Jie Chuang; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen; Lu-Yin Lin (Fuel, 2026)

Co-removal of norfloxacin and Cr(VI) by Co/N-doped carbon activating peroxymonosulfate: 1O2 oxidation coupled with interfacial electron transfer - Yaru Li; Heming Wang; Rong Qiao; Dongxu Zhou; Fuyun Deng; Gaoyang Chen; Peixin Mao; Chaolin Yang; Xiaodong Zhang (Environmental Research, 2026)

An inflammation-targeted hydrogel for the synergistic treatment of colorectal cancer and associated neuropsychiatric dysfunction - Keying Chen; Na Li; Anni Ren; Lingling Yang; Pei Xie; Yong Gao; Yanwu Li; Ying Tang; Rong Zhang; Huafeng Pan; Bangjiang Fang; Tongkai Chen; et al. (Chemical Engineering Journal, 2026)

Solar-driven green degradation of lignin toward sustainable aromatics via BiVO4/Zn4In2S7 S-scheme heterojunction - Qunshuai Li; Luxin Zhang; Weiwei Shi; Sishang Ge; Menglu Hu; Rong Chen (Chemical Engineering Journal, 2026)

Geomorphic filtering of pollen signals across a reef-to-basin transect and its implications for paleoenvironmental reconstruction in the Xisha archipelago, South China Sea - Jiani Chen; Sui Wan; Wei Li; Yi Zhong; Rong Xiang; Xiang Su; Chuanxiu Luo; Dizhu Cai (CATENA, 2026)

Heavy silicon isotope and mass-independent mercury isotope fractionation signals of Archean TTGs: Insights into the recycling of the silicified oceanic crust in the source region - Xiao Hu; Wenbin Zhu; Haizhen Wei; Runsheng Yin; Yongxiang Li; Yiwei Rong; Di Chen (Chemical Geology, 2026)

The meteorological and anthropogenic drivers of O3 and PM2.5 pollution in China's Ningbo based on WRF-CMAQ-ISAM - YuZhan Xie; Tijian Wang; Pulong Chen; Kuanguang Zhu; Tao Niu; Rong Li; Mengmeng Li; Hao Wu; Yawei Qu; Xu Liu; Congwu Huang (Atmospheric Pollution Research, 2026)

Poricoic acid A administered during DSS exposure attenuates acute colitis in mice and is accompanied by barrier-associated changes and endpoint fecal microbiota shifts - Mei Wang; Kunkun Zhang; Danli Wang; Mingtao Cao; Rong Yong; Xiangqian Li; Wenyi Chen; Chengcheng Peng; Jiale Chang; Lu Fang; Feiyang Zhou; Yuyue Wan; et al. (Journal of Natural Medicines, 2026)

Assessing cognitive impairment in epilepsy using Arterial spin-labeled (ASL) perfusion imaging - Qiuyan Chen; Jie Zhang; Rong Chen; Yameng Qin; Xu Wang; Qiang Liu; Zheng Yin; Ping Yang; Feng Rao; Longnan Wang; Mengyun Li; Yanzi Jin; et al. (Brain Imaging and Behavior, 2026)

Botany, extraction methods, chemical constituents, pharmacological activities, and food applications of Stauntonia chinensis - Chen-Yu Chang; Xiao-Yun Wang; Ke-Jia Liu; Qi Li; Shu-Yan Lu; Qin-Ge Ma; Rong-Rui Wei (Natural Product Research, 2026)

Assessing impacts of vertical mixing parameterizations on ENSO simulation in a ROMS-based hybrid coupled model - Yinnan Li; Yang Yu; Maonan Chen; Chuan Gao; Hongna Wang; Liu Yang; Rong-Hua Zhang (Journal of Oceanology and Limnology, 2026)

Acupoint hot compress for labor-pain management: a randomized, parallel-group, controlled trial - Fangfang Wang; Leyi Fu; Xinyue Li; Yuqun Pu; Lianqing Gong; Lin Zhou; Lanxiang Fu; Yaping Chen; Mali Chen; Yue Qin; Xiaoying Lyu; Ye Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Effects of Poly-γ-Glutamic Acid Application on Greenhouse Gas Emissions and GrainYield Under Different Direct-Seeding Methods in Paddy Rice - Rong Huang; Shi-hao Li; Hong-yan Li; Qian Luo; Yu-quan Fu; Qu-chen Zhou; Xiang-yu Huang; Xue-zhu Du; Feng Sheng (Journal of Soil Science and Plant Nutrition, 2026)

Cinnamoylphenethyl amides from fissistigma bracteolatum and their anti-inflammatory activities - Jin-Feng Xue; Yao-Yao Jia; Jing-Wei Lei; Yan-Jun Sun; Hui Chen; Yan-Le Zhi; Zhen-Zhu Zhao; Dong-Rong Zhu; Guo-Sheng Li; Gui-Min Xue (Natural Product Research, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Industrial waste salt pyrolysis toward zero liquid discharge: Enabling efficient organic removal and resource recovery - Zhi-Bo Li; Xiang-Lin Chang; Juan Xie; Rong Chen; Xiaochang C. Wang; Bao-Shan Xing (Journal of Water Process Engineering, 2026)

Species-specific bioaccumulation and biotransformation of antibiotics shape differential toxicological effects in a multi-level aquatic community - Bin Wang; Hailing Zhou; Mengting Li; Bingyu Shen; Lidan Zhang; Jiayi Yang; Yushi Fang; You Zi; Jinmei Chen; Yujie He; Rong Ji (Journal of Hazardous Materials, 2026)

Spatiotemporal characteristics and influencing factors of phosphorus metabolism in China's food consumption and disposal system - Shenyi Lu; Zheng Guo; Sophia Shuang Chen; Xingchun Cen; Rong Li; Giri Raj Kattel (Journal of Cleaner Production, 2026)

Reducing environmental footprints of food consumption in urban and rural China: A scenario-based optimization towards sustainable diets - Zheng Guo; Junjie Zhao; Sophia Shuang Chen; Jialong Xu; Yi Zhang; Rong Li; Yingyi Ma; Enkang Li; Giri Raj Kattel (Journal of Environmental Management, 2026)

Separation of V/Cr from the leachate of vanadium slag by solvent extraction to prepare vanadium electrolyte - Rong Jiang; Limei Chen; Qiuxiang Liu; Mingyu Wang; Guiqing Zhang; Qinggang Li; Wenjuan Guan; Shengxi Wu; XinSheng Wu (Hydrometallurgy, 2026)

Application of optimized hydrothermal, ozone and superalkali pretreatment techniques for qualitative biogas production from corn straw: A comparative assessment - Sifan Cao; Yong-Chen Han; Huqe Farhana; Xiaochang C. Wang; Rong Chen; Yu-You Li; Bao-Shan Xing (Fuel, 2026)

Chymotrypsin-based LC-MS for accurate quantification of 11 major food allergens in heat-processed foods overcoming Maillard reaction challenges - Siyi Li; Meizhen Zhou; Ruijie Chen; Yutong Xu; Yumeng Zhao; Yingnan Shencheng; Shuyan Liu; Rong Zhang; Min Gao; Yi Li; Shupeng Yang (Food Chemistry, 2026)

Corrigendum to “A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization” [Chemical Engineering Journal 532 (2026) 174382] - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Phosphorus–boron synergistic carbonization/dormancy strategy enables polyurethane foams with aging enhanced fire safety - Shuang Li; Hai-Bo Zhao; Ming-Jun Chen; Lei He; Lin Zhang; Fu-Rong Zeng; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Natural pyrite-enhanced co-culture system for simultaneous nitrate and ammonium removal under low C/N conditions: Mechanistic insights and real wastewater application - Kuang-di Xu; Pan He; Xiang-lin Liu; Lei Yu; Si-jia Li; Quan Wang; Rong-ping Chen; Ke Yin; Guang Guo; Wen-Jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Optimizing lipid retention for anaerobic membrane bioreactors treating food waste: Balancing methane enhancement and membrane fouling control - Luwei Yan; Shuangquan Zhao; Yu Xi; Yaqian Liu; Yuxin Xiao; Zhen Lei; Qian Li; Rong Chen (Bioresource Technology, 2026)

Role of the immune microenvironment in bone regeneration and progress in immune-modulating bone nanobiomaterials - Rong’an Li; Jiakang Yang; Wenjun Duan; Kexin Yang; Katong Lo; Qianming Chen; Baixiang Wang (Journal of Zhejiang University-SCIENCE B, 2026)

Comparative effects of digestion residue-derived and corn straw biochar on free-living diazotrophs in nitrogen-deficient calcareous purple soil - Junwen Zhao; Yuting Chen; Haiyan Zhang; Yulan Chen; Bing Li; Muhammad Bilal Khan; Yingjie Wu; Xiaoyan Tang; Huanxiu Li; Rong Huang; Qiang Xu; Qiquan Li; et al. (Biology and Fertility of Soils, 2026)

An Indicator System for Evaluating the Powerhouse of Meteorological Science and Technology: Design and Preliminary Application - Chaolin Zhang; Xudong Liang; Min Wen; Jianjun He; Wenjuan Zhang; Chang Liu; Qing Sun; Rong Yu; Xiaolu Yan; Zhu Zhang; Qihua Jin; Aili Shi; et al. (Journal of Meteorological Research, 2026)

Temporin-GHaR6R Peptide Ameliorates Experimental Autoimmune Encephalomyelitis by Suppressing Microglial M1 Polarization and Mitochondrial Dynamics Dysfunction - Da-Qi Zhang; Hui-Min Xu; Jing Lu; Yu-Sheng Huang; Xiao-Li Feng; Li-Jun Chen; Wen-Jie Zhao; Rong Wang; Yingxia Zhang; Qifu Li (Probiotics and Antimicrobial Proteins, 2026)

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

Corrigendum to “Progress in the application of Salmonella vaccines in poultry: A mini review” [Vet. Immunol. Immunopathol. 278(2024), 110855] - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2026)

Microbial lifestyles driven by C: N stoichiometric imbalance govern responses of carbon metabolism to nitrogen addition - Bo Kang; Rong Huang; Xun Yan; Linkang Chen; Shanghong Chen; Youlin Luo; Xiaoyan Tang; Yingjie Wu; Qi Tao; Qiang Xu; Changquan Wang; Bing Li (Soil Biology and Biochemistry, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

A data–mechanism fusion method for ships collision avoidance based on Probabilistic Velocity Obstacles - Zhuojun Yuan; Junmin Mou; Mengxia Li; Linyin Chen; Pengfei Chen; Hao Rong; Zaili Yang (Ocean Engineering, 2026)

High-performance conductive ceramic membrane coupling with electrochemical membrane bioreactor (EMBR) for advanced wastewater treatment: Optimization of fabrication approach and application conditions - Lingyi Kong; Yisong Hu; Zhenqi Xu; Qiaoqing Zhang; Guanqian Wang; Xiaobao Li; Rong Chen (Journal of Water Process Engineering, 2026)

Dual-engineered defect-rich molecularly imprinted zirconium metal organic framework platform for selective adsorption and ultrasensitive analysis of alternariol - Shi-Rong Sun; Lu Liu; Xia Wang; Yan Dong; Yan Li; Qianyun Sun; Yanfang Zhao; Xiangfeng Chen; Yong-Ning Wu; Rabah Boukherroub; Ru-Song Zhao (Journal of Hazardous Materials, 2026)

A novel mitochondrial OMA1-DELE1-HRI axis mediates polystyrene microplastics-induced blood-testis barrier dysfunction - Rong Wang; Zhen Tian; Chen Chen; Ming-Ming Zhang; Ding-Qiang Peng; Ke-Xin Liu; Yu-Tong Ren; Shuai Lin; Qiang Hong; Yan-Li Ji; Yuan-Hua Chen (Journal of Environmental Sciences, 2026)

Latitudinal gradients shape adaptive divergence of tea saponin accumulation in Camellia oleifera - Danmei Yu; Liyun Feng; Suyun Zhang; Xiaohua Liu; Huan Yang; Jie Xiao; Shang Chen; Xia Dong; Li Cheng; Yao Zhao; Jun Rong; Jian Zhang (Food Bioscience, 2026)

Mussel-inspired surface modification for high-rate and effectively complex wastewater systems purification - Minrui Zhan; Xi Zhang; Rong Liu; Manman Zhao; Wenkai Li; Huiyu Yang; Jiehao Du; Wei Chen; Shaojin Gu; Xin Liu; Bin Shang (Desalination, 2026)

Erosion depth and seasonality jointly regulate soil nitrogen transformations during early vegetation restoration in dry-hot valleys - Zhongao Tang; Taicong Liu; Zhe Chen; Li Rong; Xingwu Duan; Wenxu Liu; jinxin Fang; Jinglin Li (CATENA, 2026)

Three new lanostane-type triterpenoids with cytotoxic activity from the Ganoderma leucocontextum - Rong Fu; Xiaohong Li; Yonggang Kang; Baosong Chen; Chou Mo (Natural Product Research, 2026)

Discovery of pyrrolo[2,3-d]pyrimidine derivatives with inhibitory effect on liver cancer stem cell - Xuecong Zhang; Xuechun Chen; Liwei Wang; Yiyuan Chang; Jiaxin Li; Jijian Yang; Dongxuan Ni; Ruihan Zhang; Rong Liu; Weilie Xiao (Medicinal Chemistry Research, 2026)

An approach for detecting hemodynamic parameters in the carotid arterial system based on the priori relationship between blood pressure and arterial radius - Jin Wang; Yong-Jiang Li; Yu-Yuan Zhang; Jing-Rui Gu; Xian-Wei Wang; Dong Chen; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2026)

Debris flow vulnerability assessment in the Eastern Tibetan Plateau using integrated UAV-SLAM 3D reconstruction: Shuihaizigou Gully case study - Haoyu Li; Jianqiang Zhang; Yunyuan Li; Lili Zhang; Zaiyang Ming; Rong Chen (Landslides, 2026)

Layered manure facilitates phosphorus mobilization mediated by putative keystone taxa among phoD-harboring bacteria - Linkang Chen; Rong Huang; Xiaoyan Tang; Bo Kang; Yijian Zheng; Zongjin Zhang; Changquan Wang; Bing Li (Applied Soil Ecology, 2026)

Microbial Community Structure, Rather Than Diversity, Predicts Plant Yield Under Global Change - Xu Xu; Jie Liu; Shicong Chen; Shanshan Liu; Menghui Dong; Qingfeng Xu; Peiyao Yang; Ting Sun; Longzheng Wang; Hemu Zhang; Yang Yang; Qirong Shen; et al. (Global Change Biology, 2026)
Under global change, terrestrial plants adjust their physiological metabolism alongside adaptive restructuring of rhizosphere microbial communities, yet the mechanistic links between plant phenotypic plasticity and microbial consortia remain unclear. Here, we conducted a meta‐analysis of 272 global‐change experimental comparisons and found that, among all global change factors examined, nitrogen addition exerted the strongest effects on both plant yield and microbial community assembly. Plant adaptive responses were more strongly associated with shifts in microbial community structure than with changes in alpha diversity. Microbial community structure reorganization was associated with increased soil carbon availability, whereas higher local microbial beta diversity constrained the magnitude of structural change. Based on a reanalysis of published amplicon sequencing datasets, we found that more stable and complex microbial networks, enriched with Proteobacteria and Actinobacteria, were associated with higher plant yield. These findings underscore plant‐microbe co‐adaptation under global change, highlighting microbial community structure as a key mediator linking soil environmental shifts to plant adaptive performance.

HDAC inhibition reprograms stem cell fate to suppress infantile hemangioma vasculogenesis - Qiming Chen; Hao Rong; Chao Liu; Jiang Li; Jiawei Zheng; Qian Bian (Angiogenesis, 2026)

Isolation, identification, and disease-protective potential of Pseudomonas monsensis DBFF02 against Saprolegnia infection in grass carp - Guofan Zhang; Kunyan Li; Yuyuan Peng; Simei He; Chen Li; Rong Fan; Jiajie Xie; Linger Qian; Xinran Long; Jiayi Wang; Jiatao Yang; Yanmin He; et al. (Aquaculture, 2026)

Unraveling the flame retardant mechanism of protein-rich matrix recovered from anaerobic sludge: The governing role of microstructural characteristics - Bo Zhang; Gaojun Wang; Yinghong Dong; Qian Li; Yu-You Li; Rong Chen (Water Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A novel phytoformula targeting lipid peroxidation inhibition attenuates UV-induced skin photoaging - Ling-Ping Wu; Wei Chen; Qian-Pei Lin; Shi-Yun Feng; Jin Dai; Qiong-Yi Zhang; Wen-Yi Chen; Hiroshi Kurihara; Xiao-Min Li; Shu-Hua Ouyang; Yi-Fang Li; Rong-Rong He (PharmaNutrition, 2026)

Corrigendum to “Revisiting the South China Sea MORBs: Mg isotope and whole-rock geochemical constraints” [MARGO 465C, 107164] - Yidi Hong; Tao Wu; Chunfeng Li; Xuegang Chen; Jianggu Lu; Haiou Gu; Rong Xu (Marine Geology, 2026)

Remediation effects of humic acid and hydroxyapatite on cadmium-contaminated alkaline wheat soil and its microbial community response: A field trial - Yineng Lu; Haoyu Yue; Rong Tan; Zihao Ding; Geng Chen; Shuangting Zhang; Ziyi Li; Ram Proshad; Xiuwen Cheng; Zhuanjun Zhao (Journal of Environmental Sciences, 2026)

High-efficiency solar-driven photothermal membrane distillation via permeate-side interfacial heating - Qian Yu; Mengfei Xie; Rong Chen; Kuiling Li; Liqiu Zhang; Bo Pan; XueJun Pan; Junhui Zhang; Dan Qu (Desalination, 2026)

Elevated CO2 accelerates mineral-protected organic carbon loss in the upland rhizosphere after paddy drainage - Xun Yan; Zhifan Li; Bo Kang; Tao Li; Linkang Chen; Junwen Zhao; Bing Li; Youlin Luo; Yingjie Wu; Rong Huang; Xiaoyan Tang; Qiang Xu; et al. (CATENA, 2026)

Impacts of balconies on air quality within idealized building array: CFD modelling with solar radiation - Guoxing Chen; Guoqiang Zhang; Yanni Liu; Riyi Li; Li Rong (Building and Environment, 2026)

Genome-wide Identification and Expression Analysis of the ABF Gene Family in Achnatherum splendens - Shan Yin; Mingsu Chen; Ming Hu; XiaoYing Li; Jingru Wang; Jiahuan Niu; Zhangqi Song; Huan Yang; Hongbing Li; Rong Li (Plant Molecular Biology Reporter, 2026)

Novel Method for Preparing Pseudo-Male Common Carp by Inducing Secondary Female-to-Male Sex Reversal Under High Temperature Conditions - Yulai Wei; Yi Rong; Kuangxin Chen; Yongming Li; Yanlong Song; Binbin Tao; Ji Chen; Wei Hu (Marine Biotechnology, 2026)

Anomaly analysis and comprehensive evaluation of geochemical exploration for oil and gas in the Lindian area, Northern Songliao Basin - Xiaohui Lin; Fazhun Rong; Kewei Xu; Yu Zou; Wu Li; Yinjie Chen (Geosciences Journal, 2026)

Novel prenylated diketopiperazines with anti-osteoclastogenic activity from the deep-sea-derived Penicillium limosum ZEN48 - Yong Zhang; Yan-Qing Guo; You Li; Zheng-Biao Zou; Zhe-Wen Chen; Rong Zhao; Robert J. Capon; Tai-Zong Wu; Chun-Lan Xie; Xian-Wen Yang (Marine Life Science & Technology, 2026)
A systematic chemical investigation of the deep-sea-derived fungus Penicillium limosum ZEN48 resulted in the isolation of four new indole-diketopiperazine alkaloids, limopiperazines A–D ( 1 – 4 ), alongside 16 known analogues ( 5 – 20 ). The structures of the new compounds were determined through comprehensive spectroscopic analysis, quantum chemical calculations, X-ray crystallography, and biogenetic considerations. Limopiperazine C ( 3 ) potently inhibited osteoclast differentiation and disrupted actin ring formation. Integrated RNA sequencing, RT-qPCR and molecular docking revealed that limopiperazine C exerts the anti-osteoclastogenic effect by modulating the ferroptosis signaling pathway via targeting heme oxygenase-1 (Hmox-1), positioning it as a promising lead compound for developing anti-osteoporotic agents.

Commentary: the TSP-1-CD47-integrin α4β1 axis—deciphering pathogenic mechanisms and therapeutic horizons in rheumatoid arthritis - Jie Guo; Feng-yi Mai; Xin-yu Li; Yu Liu; Jing-rong Liang; Xing-long Li; Chen-guang Li (Inflammation Research, 2026)

Hormonally and chemically induced male-to-female sex reversal is independent of Y-chromosome number in common carp - Kuangxin Chen; Yuanqi Guo; Yi Rong; Zhaoxian Li; Mouyan Jiang; Rui Li; Xiya Zhang; Yongming Li; Yulai Wei; Yanlong Song; Ji Chen; Binbin Tao; et al. (Aquaculture, 2026)

A multicomponent Fc-fused subunit vaccine induces cross-protective immunity against porcine reproductive and respiratory syndrome virus QYYZ-like and NADC30-like strains - Linxing Tian; Zhengdan Lin; Mengxi Pan; Yanwen Wen; Mingxing Lu; Shudan Liu; Chao Zhang; Zhenxiang Rong; Jiahui Ma; Ruiqu Zhou; Nan Cao; Xinghua Chen; et al. (Veterinary Microbiology, 2026)

Tumor-associated bacterial effectors: novel frontiers in tumor biology and immunity - Jia-Hao Dai; Ying-Qi Lu; Sen-Yu Feng; Xi-Rong Tan; Li-Li Li; Yue-Can Zeng; Jian-Zhou Chen; Jun Ma; Na Liu (Science Bulletin, 2026)

A germline-specific vesicular structure licenses mRNA activation during spermiogenesis and is hijacked in gastric cancer - Mingxi Liu; Zerui Wang; Yinuo Li; Qingsong Xie; Zhuang Xiao; Xuezhi He; Guanxiong Wang; Yang Gao; Yini Zhang; Lin Zheng; Xun Xia; Lujie Chen; et al. (Science Bulletin, 2026)

HGS+ enlarged vesicular compartments serve as the sites for coronavirus assembly at later infection stage - Xubing Long; Buyun Tian; Rongrong Chen; Rong Bai; Jinping Yang; Yushuang Fang; Xinyue Fu; Yanhong Xue; Wei Ji; Tao Xu; Zonghong Li (Science Bulletin, 2026)

High-resolution point source pollution database boosts SWAT-QUAL2K coupled model for multi-scale nitrogen and phosphorus management - Yang Bi; Yanxin Zhao; Yi Rong; Ningtong Li; Kai Huang; Yan Chen (Journal of Cleaner Production, 2026)

Quercetin ameliorates intestinal barrier dysfunction by suppressing the PKCα/MLCK signaling pathway in piglets - Qiuyu Chen; Huadi Mei; Mengyao Fang; Yiyan Cui; Ting Rong; Dun Deng; Zhimei Tian; Min Song; Zhenming Li; Zhichang Liu; Xianyong Ma; Miao Yu (Food Research International, 2026)

Methionine-driven covalent chelation of Zn2+ by linusorb: a paradigm in hydrophobic cyclic peptide metal binding - Yi-kang Zhang; Du-jian Deng; Zhong-yi Luo; Wan-nan Wang; Jun-le Li; Shao-rong Zhang; Jia-li Li; Jia-zi Chen; Yong Wang; Zi-zhe Cai (Food Chemistry, 2026)

Lipid oxidation-mediated protein–starch interactions in walnut cookies: Influence of oil composition on microstructure, texture, and starch retrogradation - Li Fang; Yujin Zhang; Rong Chen; Yuanfa Liu; Xiuhang Chai (Food Chemistry, 2026)

Comprehensive review of endogenous hazardous compounds in carbohydrate- and lipid-containing foods generated during thermal processing: formation mechanisms, metabolism and harm, regulatory frameworks, mitigation strategies, and analytical methods - Yawen Rong; Fei Kong; Sam Fong Yau Li; Xiaoping Yu; Jun Huang; Quansheng Chen (Food Chemistry, 2026)

A Serpine1-F2-PAR1 axis facilitates apoptosis and disease severity during GCRV infection in grass carp - Yangyang Li; Liangming Chen; Bin Gui; Changchun Yu; Jinyan Lei; Yuxuan Shao; Haiping Liu; Zuoyan Zhu; Yaping Wang; Rong Huang (Fish & Shellfish Immunology, 2026)

The climatic response of inter- and intra-annual tree ring stable carbon isotopes of larch trees in the Qinling Mountains, central China - Mingyang Sun; Chao Li; Rong Fan; Yuting Fan; Feiyu Chen; Yuanjie Wang; Huan Zhang; Ninglian Wang (Dendrochronologia, 2026)

Fe-regulated AnMBR for carbon & phosphorus co-recovery and membrane fouling control - Ying Dong; Rong Chen; Jifei Chang; Fengai Yang; Zhen Lei; Xin Wang; Nan Li (Chemical Engineering Journal, 2026)

Magnetic biochar combined with digestate bioaugmentation synergistically accelerates the recovery of a collapsed anaerobic digestion system - Bao-Shan Xing; Yong-Ning Feng; Jia-Yi Liu; Yi Zhang; Guangyin Zhen; Samir Ibrahim Gadow; Rong Chen; Xiaochang C. Wang; Yu-You Li (Chemical Engineering Journal, 2026)

Self-powered antimony oxide-coated palladium telluride/p-Silicon heterojunction DUV-MIR photodetector towards non-invasive diagnosis of diabetes - Jiayi Sun; Yuting Niu; Chen Rong; Zhikun Pang; Xinyi Han; Ningnuo Xiang; Lei Zhu; Xiaofang Li; Bo Peng; Cuicui Ling (Chemical Engineering Journal, 2026)

Insights to how tubular pore biochar affects anaerobic digestion of waste activated sludge: Performances and mechanisms - Ze-Mu Li; Ai-Hua Li; Qing-Bin Meng; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Photoelectron-driven modulation of carbon metabolism enhances hydrogen production in a ZnIn2S4-Shewanella oneidensis biohybrid system - Xue-Meng Wang; Hao-Yu Li; Kai-Li Wang; Zhi-Xuan Zhang; Yu-Xin Cao; Ya-Lian Ma; Rong Chen (Bioresource Technology, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

Evaluation of protein and metabolic engineering strategies on (−)-α-bisabolol production by Escherichia coli - Jiayi Ma; Rong Fang; Xiaoyuan Yue; Hui Jiang; Qixuan Kong; Tiankuo Jiang; Jiale Yu; Chang Zhou; Yuanyuan Xia; Wei Shen; Haili Liu; Yaqin Shen; et al. (Systems Microbiology and Biomanufacturing, 2026)

Mechanisms by Which Humic Acid Reduces Copper Toxicity in Citrus Roots Based on Omics and Physiology - Wei-Tao Huang; Rong-Rong Xie; Liang-Yuan Tong; Tian-Tian Xia; Jiuxin Guo; Ning-Wei Lai; Zeng-Rong Huang; Lin-Tong Yang; Li-Song Chen (Journal of Plant Growth Regulation, 2026)

Sorption and degradation of α-terpineol in soils with distinct physicochemical properties - Huan-Feng Chen; Zi-Jun Yang; Hai-Rong Chen; Hai-Ming Zhao; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Lei Xiang (Environmental Geochemistry and Health, 2026)

Multidisciplinary modeling and dynamic Kriging assisted optimization for suborbital reusable launch vehicle - Teng Long; Haoda Li; Renhe Shi; Rong Chen; Baoshou Zhang; Nianhui Ye (Advances in Space Research, 2026)

Human MAITregs possess diverse TCR repertoires and are functionally supported by glycolysis - Maoyu Tang; Xinying Li; Xudong Yang; Changfeng Zhao; Yuwei Zhang; Sanwei Chen; Zhenghui Ye; Liujin Hou; Yusheng Chen; Rong Lv; Hongchuan Zhao; Xiaowen Cheng; et al. (Science China Life Sciences, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Immunogenicity and safety of an Escherichia coli-produced 9-valent HPV vaccine in adolescents aged 9 to 17 compared with young women - Yulin Jing; Xiaowen Hu; Li Zhang; Jiangyahui Wang; Fei Yang; Rong Wang; Ying Jiang; Lingling Nie; Zhongqiang Jin; Xuecheng Liu; Sihai Li; Chao Du; et al. (Science Bulletin, 2026)

Aeration strategy and nitrogen loading for stable partial nitrification coupled with oxygen-permeable membranes: Long-term performance, biofilm characteristics, and microbial succession - Xifang Tang; Bao-Shan Xing; Yong-Ning Feng; Ling-Hu Li; Xin-Xin Sun; Yu-You Li; Rong Chen (Journal of Water Process Engineering, 2026)

Association between plasma trace metals and non-alcoholic fatty liver disease among rural women in Southern China - Qiumei Liu; Xiaolin Li; Yufu Lu; Kaisheng Teng; Xiaoting Mo; Linhai Zhao; Songju Wu; Jiahui Rong; Qinyi Guan; Lei Luo; Tiantian Zhang; Yujian Liang; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

The transcription factor SlPLATZ22 negatively regulates salinity tolerance in tomato plants - Xin Li; Fei Ding; Niannian Zhou; Zheng Chen; Jiahui Huang; Fangling Jiang; Carl-Otto Ottosen; Ron Mittler; Rong Zhou; Zhen Wu (Journal of Plant Physiology, 2026)

Aerobic biodegradation of acesulfame by sediment-enriched microbial consortia: Kinetics, pathway, and microbial mechanism - Xiaoxue Zhang; Jianwei Chen; Yuxuan Li; Rong Tang; Tianyue Zhu; Yong Yuan (Journal of Environmental Management, 2026)

Fe/Cu-γ-Al2O3 catalyst for pilot-scale internal circulation Fenton degradation of methyl orange: performance and mechanism - Dekai Fan; Yanran Lin; Peng Zhu; Yingwen Zhang; Bang Yao; Li Chao; Zhuangzhuang Jia; Jianjun Dai; Yingrui Ning; Rong Xiao; Chen Chen; Lei Gao; et al. (Journal of Environmental Management, 2026)

Evaluation of near infrared spectroscopy for direct detection of common microplastics contamination in camel Milk powder - Chunxu WAN; Yin LIU; Jing XIE; Feng CHEN; Huijie SHEN; Rong LI (Food Chemistry, 2026)

High hydrostatic pressure mitigates light-induced degradation of volatiles and phenolic compounds in seabuckthorn pear blends - Jianfeng Wang; Yonghao Chen; Rong Zhang; Shengbin Ma; Faisal Eudes Sam; Jixin Li; Yang Bi; Yumei Jiang (Food Chemistry, 2026)

Precise pH control and synergistic interaction of raw materials improve the quality of stewed beef: multi-omics analysis of tenderization mechanisms and flavor restructuring - Yan Shen; Zezhu Du; Jinya Dong; Yuanfeng Chen; Huiqing Luo; Siyu Zhou; Cheng Gong; Shikuan Zhao; Zhiyu Li; Lihui Yu; Rong Geng; Xiaocui Du; et al. (Food Chemistry, 2026)

Using integrated multi-omics and molecular docking to decode stone epiphytic culture as a strategy for enhancing flavonoids and bioactivity in Dendrobium officinale leaves for functional tea development - Jing Li; Rong Zhou; Yingyue Hou; Yichang Chen; Shaohao Xie; Jinyu Wu; Jiang Chen; Hongbin Hou; Guangying Du (Food Bioscience, 2026)

Nitrogen doped graphene quantum dots modified a crystalline zinc phosphite based non-enzymatic electrochemical sensor for the ultra-low detection of tyramine - Pi-Chen Wei; Asit Kumar Panda; Yu-Chung Chang; Yi-Rong Li; Todd Hsu; Chih-Min Wang (Food Control, 2026)

Synergistic effects of polystyrene microplastics and 17α-methyltestosterone on immune and oxidative stress responses in the gill and liver of Gobiocypris rarus - Yibo Jia; Lu Cao; Tongyao Li; Haiyan Zhao; Gen Chen; Zijun Xiong; Weiya Rong; Qing Liu; Weiwei Wang; Jing Song; Xianzong Wang; Yu Liu; et al. (Fish & Shellfish Immunology, 2026)

Sustained performance and microbial succession in novel artificial rumen system coupling dynamic membrane with methanogenic granules for acid absorption - Xiang-Lin Chang; Bao-Shan Xing; Yu Qin; Juan Xie; Zhi-Bo Li; Xiaochang C. Wang; Rong Chen; Yu-You Li (Bioresource Technology, 2026)

Integrative bulk and single-cell transcriptomic analyses reveal nucleus pulposus cell fibrosis as a therapeutic target in intervertebral disc degeneration and identify quercetin as a potential antifibrotic agent - Peilin He; Jun Tao; Guo Li; Ye Mu; Rong Hu; Junming Chen; Wenqi Feng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Efficacy and Safety of Temozolomide for the Treatment of Advanced or Recurrent Ependymoma: A Meta-Analysis - Rong Zhang; Binyan Liu; Zhuang Kang; Shenglan Li; Yingfan Sun; Jiachen Wang; Xin Yang; Shuo Yin; Feng Chen; Wenbin Li (Journal of Pharmaceutical Innovation, 2026)

Metallogenic Age of the Qianjiadian Uranium Deposit—Evidence from Fluid Inclusions and (U-Th)/He - Ruxin Ding; Yangshijia Li; Zilong Li; Rongli Huang; Minqiang Cao; Xingzhou Chen; Hui Rong; Heping Zou (Journal of Earth Science, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Chronic Excessive Exposure to Fluoride Impairs the Intestinal Mucosal Barrier to Cause Inflammatory Response and Microbiome Dysbiosis in Rats - Jia-Rong Zhang; Yi-Wen Li; Hong-Xuan Chen; Yi Luo; Ru-Ming Liu; Jian-Bin Wang; Ning-Ning Liu; Jian-Hui Xiao (Biological Trace Element Research, 2026)

SVA virus-like vesicle vaccine based on VEEV-VSVG vector elicits efficient immune responses and protection in swine - Zhenxiang Rong; Mingjin Jiao; Nan Cao; Mingxing Lu; Shudan Liu; Chao Zhang; Liuqing Wei; Yamei Li; Huanchun Chen; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2026)

Coordination-tailored conductive metal-organic frameworks boost CO2 electroreduction to ethylene for cascade ethylene glycol production - Hui Guo; Shao-Shuai Zhao; Duan-Hui Si; Weijin Li; Zi-Ao Chen; Rong Cao; Roland A. Fischer; Yuan-Biao Huang (Science Bulletin, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

Upcycling anaerobic digestion methane to single-cell protein as a low-carbon strategy - Pan-Long Lv; Qing-Rui Hu; Yu-Yang Hu; Wenjing Gong; Qian Li; Rong Chen (Resources, Conservation and Recycling, 2026)

Differential spatiotemporal distribution and assembly mechanisms of microeukaryotic generalists vs. specialists in the Bailong River Basin - Lingyun Chen; Rong Tang; Haifeng Du; Jianchuan Li; Alan Warren; Chengzhi Mao (Journal of Environmental Sciences, 2026)

Identifying the genesis and evolution of geothermal water in the coal mining area, North China: Insights from hydrochemistry and δ2H, δ18O, δ13C, δ34S and 87Sr/86Sr isotopes - Jie Zhang; Herong Gui; Luwang Chen; Manli Lin; Huifang Rong; Jun Li; Ruirui Li; Mingda Cao (Geothermics, 2026)

One stone, two birds: Preparation of nutritionally fortified and easy-to-swallow 3D printed pea protein gel based on high internal phase emulsions - Wei Liang; Junhong Xie; Qiannan Zhao; Chenghong Jiang; Xiaofeng Zhan; Mingrong Chen; Lu Zhang; Chuan Li; Jianhua Rong; Yang Hu (Food Hydrocolloids, 2026)

A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Reduced graphene oxide enhances emerging contaminants removal in anaerobic wastewater treatment: Synergistic role of adsorption and microbial metabolism - Lianxu Wang; Zixin Zhang; Youfei Zhou; Zhen Lei; Yuan Yang; Yu-You Li; Rong Chen (Bioresource Technology, 2026)

Pyrite-driven redox modulation improves microbial tolerance to furan inhibitors in hydrogen production from lignocellulosic hydrolysates - Hao-Yu Sun; Xin Xu; Si-Jia Li; Lei Yu; Quan Wang; Rong-Ping Chen; Ke Yin; Guang Guo; Xu Sun; Yu-ting Xin; Wen-jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Comprehensive genomic analysis of the maize ACP gene family reveals ZmACP1-mediated salt stress tolerance in Arabidopsis - Yunhao Wu; Junyu Chen; Hanqiu Ge; Xing Rong; Yuchen Wang; Meiwang Zhang; Zhigang Li; Yingrui Xi; Junfeng Tang; Junyi Li; Ping Li; Baohua Wang; et al. (Plant Cell Reports, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

Biological and mineral amendments synergistically coordinate soil micro-food web to enhance multifunctionality - Baijing Zhu; Huaxiu Chen; Han Li; Qiang Zhu; Wenfeng Tan; Jiao Feng; Yu-Rong Liu (Applied Soil Ecology, 2026)

Rhizosphere fungal community and microbial networks shape N2O emissions and crop yield in a rice-rapeseed rotation system under varying nitrogen levels: A case study from Southwest China - Jin-meng Li; Rong Zhao; Tian-yang Ye; Cong-hua Zhu; Jin Chen; Ping Huang; Xue-qing Yang (Agriculture, Ecosystems & Environment, 2026)

Differential Bottom‐Up Control of Planktonic and Sedimentary Bacterial Communities by Phytoplankton and Extracellular Enzymes in an Asymmetric River Confluence - Yi Li; Huijuan Huang; Bi Luo; Rong Wang; Bing Yu; Xian Xu; Zhaotong Chen; Yushan Li; Zhiwei Zhu (Molecular Ecology, 2026)
Bacterial community dynamics underlie ecosystem functioning in river networks, yet how different bacterial lifestyles respond to bottom‐up biotic drivers under confluence‐induced hydraulics remains unclear. Here, we quantified spatial heterogeneity in free‐living (FL), particle‐associated (PA) and sedimentary (S) bacterial assemblages, coupled with phytoplankton and extracellular enzyme profiles, at the Yellow River‐Fenhe River confluence during the summer wet season. Clear habitat partitioning emerged, with stronger divergence at the water–sediment interface than between the two planktonic fractions (FL vs. PA). Hydrological source tracking showed that Fenhe River‐derived taxa dominated both water and sediment within the confluence reaches, whereas Yellow River lineages prevailed in the downstream reaches. Community assembly shifted hierarchically: homogeneous selection dominated FL assemblages but declined progressively toward PA and sedimentary fractions, while dispersal limitation intensified in tandem with niche contraction. Multivariate analyses showed that in addition to physicochemical factors, enzyme activity is the strongest factor predicting FL communities, explaining 43.6% of variability, whereas the phytoplankton community best predicted PA communities (68.8%). Sedimentary communities correlated weakly with phytoplankton associations (21.8%) and showed no significant link with enzyme activity. Our findings identify phytoplankton communities and enzymatic potential as key bottom‐up drivers whose relative importance varies with bacterial lifestyle, providing mechanistic insight into biophysical dynamics within river‐confluence ecosystems.

Advances in natural biomacromolecule-based Janus materials: preparation, applications and future prospects in food science - Ying Xu; Xuan Tao; Liubin Li; Yao Chen; Rong He; Xingrong Ju; Zhigao Wang (Critical Reviews in Food Science and Nutrition, 2026)

Hydrogeophysical Imaging and Joint Interpretation of Rainfall Infiltration on an Embanked Slope in the Mid-Lower Yangtze Hilly Region - Rong-wen Guo; Chen-yang Li; Zhuo Liu; Deng-kang Wang; Ming Yu (Applied Geophysics, 2026)

Butyrate supplementation in sows promotes offspring embryonic muscle development by upregulating HDAC-mediated H3K27ac levels and myogenic gene expression - Hao Zuo; Chen Li; Xiaoyu Niu; Zhibo Ma; Zhifeng Wu; Zeyang Gao; Liqian Sun; Yiming Jia; Mingfei Zhu; Litong Wang; Rong Zheng; Bo Zuo (Science China Life Sciences, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

Sustained polyhydroxyalkanoate recovery from fermentative food wastewater in a one-stage mixed microbial culture system under aerobic dynamic discharge strategy: Effects of organic loading rate and substrate composition - Xiang Zhang; Ji Zhang; Gaojun Wang; Kexin Wang; Yanfang Ma; Qian Li; Yu-You Li; Rong Chen (Journal of Cleaner Production, 2026)

Ti(IV)-incorporated covalent organic frameworks for efficient dark-photocatalytic reduction of U(VI) - Li-Ling Chen; Cheng-Peng Niu; Rui Zhang; Yun-Peng Wu; Zhen-Wen Zhang; Bin Lin; Cheng-Rong Zhang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2026)

Microbial generalists and specialists in permafrost demonstrate disparate responses to extreme environments - Chengzhi Mao; Pingping Xu; Ramiro Logares; Bing Ma; Jianchuan Li; Rong Tang; Jiayuan Wang; Xiaosong Wang; Jinglan Wang; Yitong Wang; Yuxiu Chen; Lingyun Chen (Journal of Environmental Management, 2026)

Impact of complex inhibitors in straw hydrolysates on xylose-fermenting Saccharomyces cerevisiae and inhibitor-tolerant strain construction - Xue-Xue Ji; Bo Li; Rong-Rong Chen; Zi-Yuan Xia; Cai-Yun Xie; Yue-Qin Tang (Fungal Biology, 2026)

Effect of freeze–thaw treatment on physicochemical and antioxidant properties of Chinese hawthorn fruit and its juice - Rong Li; Chang Ma; Falong Du; Jiawei Cui; Yunfeng Hu; Junran Chen (Food Chemistry, 2026)

Rapid quantitative real-time analysis and visual detection of Escherichia coli in meat by direct PMAxx-VPCR - Jiaqi Cui; Tingting Zhao; Wenjun Song; Huilin Li; Yan Chen; Rong Chen (Food Control, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Self-assembly of bayberry-like porous BiVO4 nanospheres for self-powered marine underwater optical communication - Ping Wang; Shuai Ren; Kun Fu; Yizhou Lv; Yayue Wang; Ping Rong; Weipeng Chen; Jianhua Zhang; Xifei Li; Qi Yu (Chemical Engineering Journal, 2026)

Microwave-assisted pyrolysis of dyeing sludge: Reaction kinetics, elemental transformation, and heavy metal migration - Dekai Fan; Rong Xiao; Wahab Nasarul; Chunbao Zhou; Yingwen Zhang; Bang Yao; Li Chao; Jianjun Dai; Gul Urooj; Yingrui Ning; Peng Zhu; Chen Chen; et al. (Chemical Engineering Journal, 2026)

Sulfur-induced electronic coupling in g-C3N4/Ti3C2Tx-MXene 2D/2D heterojunction enables highly efficient solar-driven disinfection - Rong Ma; Xiaochun Tao; Shuo Li; Chenglong Chen; Qinqin Liu; Shaosheng Rao; Juan Yang (Chemical Engineering Journal, 2026)

Innovative utilization of waste printed circuit boards and coal gangue/ash for multifunctional glass-ceramics: structure-property insights via data-driven analysis - Yingwen Zhang; Lei Gao; Li Chao; Bang Yao; Dekai Fan; Chen Chen; Rong Xiao; Yingrui Ning; Peng Zhu; Urooj gul sandilo; Abeanezer Lukas Bassa; Nasarul Wahab; et al. (Chemical Engineering Journal, 2026)

Crystal-facet regulation of SnO₂ {221} and {110} for selective detection of dimethyl carbonate and H2 gases in battery thermal runaway - Xun Shen; Aijun Yang; Ruochen Ding; Kehan Bo; Jifeng Chu; Pengxu Chen; Chenhui Li; Hongye Yuan; Huan Yuan; Mingzhe Rong; Xiaohua Wang (Chemical Engineering Journal, 2026)

Kinetics of air mixing–anaerobic digestion: High organic substrate concentrations enhance system resistance to oxygen stress - Kailun Song; Huan Chen; Yue Zhao; Li Chen; Rong You; Yilin Wang; Hongnan Yang; Wenguo Wang; Liangwei Deng (Chemical Engineering Journal, 2026)

Hydroxybutyl chitosan-based thermosensitive hydrogel enhanced osteoporotic bone regeneration through sustained release of alendronate and BMP-2 - Mingyuan Lei; Haibing Liu; Qiang Zhong; Libo Zhao; Jingwen Liu; Huaming Mai; Yuheng Zhang; Hongyu Wang; Yourong Chen; Rong Chen; Yixin Xu; Hao Li; et al. (Carbohydrate Polymers, 2026)

Operational thresholds and microbial mechanisms in high-solid anaerobic membrane bioreactors treating swine wastewater: from process performance to metabolic pathways - Yu Li; Gaojun Wang; Yuan Yang; Lingsen Liu; Xiaohong Dang; Yu-You Li; Rong Chen (Bioresource Technology, 2026)

Adsorption of Oxytetracycline Hydrochloride by Oxidatively Modified Biochar Particles: Performance and Mechanism - Rong Chen; Jianlin Zhou; Lingling Wang; Weiyin Liu; Zeyu Dai; Zhang Chen; Guoliang Chen; Zhixian Li (Water, Air, & Soil Pollution, 2026)

Plant-soil feedback driven by root-associated fungal communities accelerates the secondary succession of bare saline-alkaline grassland patches - Xiaona Zheng; Yuhong Yin; Dan Yang; Jingjuan Bi; Wenlong He; Siya Li; Xiao Liang; Jigui Chen; Rong Wang; Zhiying Guo; Xing Li; Tao Zhang; et al. (Plant and Soil, 2026)

Novel 2-aminothiazole derivatives incorporating 9-alkyl purine moiety: design, synthesis, crystal structure, and bioactivity evaluation - Song Bai; Suran Wan; Miao Li; Rong Wu; Shouying Tang; Fang Wang; Lijun Chen; Xiaokang Lv; Xian Wei; Shuang Feng; Miaohe Zhang (Molecular Diversity, 2026)

Biota occurrence, accumulation, disposition and toxic effect of chlorinated paraffins - Huiming Zhang; Yutong Yang; Mu Zhang; Xue Li; Yan Zhang; Shufen Han; Rong Chen; Jun Yang; Jianyun Zhang (Environmental Geochemistry and Health, 2026)

Fabrics of forsterite in CBa chondrite Sierra Gorda 013 - Rong Li; Wei Chen; Chun-Hui Li (Acta Geochimica, 2026)

Fatal infection of a novel canine/human reassortant H3N2 influenza A virus in the zoo-housed golden monkeys - Xia Wen; Rong Chen; Yingjun Lv; Jinzhu Geng; Jingjing Guo; Yaru Sun; Aohan Yang; Yuhao Dong; Meirong Li; Changlin Deng; Guodong Wang; Yongjie Liu (Veterinary Microbiology, 2026)

Field-free topological spin textures enable spin selectivity for spin light-emitting diodes - Yongping Wei; Shuo Cao; Chenhao Zhang; Xinran Wang; Sihao Ren; Hongshu Li; Yi Yang; Jiangpeng Zhou; Mingyu Chen; Shiming Wu; Weisheng Zhao; Xichao Zhang; et al. (Science Bulletin, 2026)

Lithium ions protected orbital symmetry enables reversible oxygen redox in layered manganese-based cathodes - Ang Gao; Shiguang Zhang; Xiaohui Rong; Qinghua Zhang; Ting Lin; Yichi Wang; Yujie Chen; Valentina A. Bocharova; Weiguang Lin; Shiyu Wang; Pengxiang Ji; Hongwei Li; et al. (Science Bulletin, 2026)

Effects of state of charge on characteristics of particle emissions from lithium nickel cobalt aluminum oxide/ silicon-carbon cylindrical batteries during thermal runaway - Weifeng Li; Jie Liu; Yao Xue; Zhenhai Gao; Deping Wang; Shuli Chen; Xinqi Liu; Changru Rong; Jiawei Shi (Process Safety and Environmental Protection, 2026)

Effects of biochar on humification in Cu-rich pig manure composting under continuous high temperature: Microbial mechanisms - Xuehan Liu; Mengtong Li; Xiaochang Wang; Yanan Yin; Rong Chen (Process Safety and Environmental Protection, 2026)

Magnesium deficiency limits electron transport efficiency and photosynthesis, and induces oxidative stress in tobacco - Rong-Rong Xie; Jingjuan Gao; Changzheng Wu; Jinping Guo; Qian Cheng; Hailu Wang; Tinmin Liang; Jianjun Lu; Chaoyuan Zheng; Liangquan Wu; Li-Song Chen; Songbiao Chen; et al. (Plant Science, 2026)

Electrohydrodynamic (EHD) drying of Polygonatum sibiricum: Kinetics, physicochemical quality, and energy efficiency analysis - Xin Li; Yunfeng Wang; Ming Li; Phavady Phoodthahaksa; Jiangtao Rong; Huai Chen; Qingyun Li; Xueping Tang; Min Xu; Tarek Kh Abdelkader (Journal of Stored Products Research, 2026)

Typhoon-induced cascade effects on hydrological and biogeochemical dynamics in estuary-coast continuum: Insights from multidisciplinary observations and model forecasting in Zhanjiang Bay, China - Huizi Long; Peng Zhang; Jibiao Zhang; Menghan Gao; Binbin Fan; Zhangxi Hu; Zhihao Li; Rong Chen (Journal of Hydrology, 2026)

Quantification and geological implications of manganese, barium, and copper observed by MarSCoDe LIBS at Zhurong landing site on Mars - Yuxuan Luo; Zhaopeng Chen; Jianjun Liu; Yizhong Zhang; Jingjing Zhang; Zhibin Li; Xin Ren; Xiangfeng Liu; Zhenqiang Zhang; Weiming Xu; Guolin Hu; Shaojin Han; et al. (Icarus, 2026)

Coordinated horizontal transfer of multiple genes assembles a carotenoid biosynthesis pathway in aphids - Rong Hu; Jun Wu; Siying Li; Peiyu Yang; Gang Wu; Changying Niu; Shuai Zhan; Yazhou Chen (Insect Biochemistry and Molecular Biology, 2026)

Remediation of ternary heavy metal-polyethylene microplastics co-contaminated soil using co-modified biochar with deep eutectic solvent and warm patch: competitive interactions, mechanistic insights, and microbial community response - Luxin Zhang; Xiaobing Liu; Sishang Ge; Weiwei Shi; Rui Zhang; Chaoyang Li; Rong Chen (Environmental Research, 2026)

The low R = d/d high-entropy strategy enables high-performance sodium layered oxide cathode materials - Jun-Jie Liao; Min Wen; Wei-Wei Yuan; Qi-Lin Zheng; Kang Chen; Fu-Sheng Zhou; Zhen-Xin Qiu; Su-Yun Wang; Li-Li Wang; Lituo Zheng; Yiyin Huang; Jia-Xin Li; et al. (Chemical Engineering Journal, 2026)

Synergistic (002) texturing and interfacial CuZn5 alloying on 3D ridge-like Cu substrates for dendrite-free Zn anodes - Xiangzhong Kong; Zicong Wang; Yong Liu; Zhilong Yao; Xi Chen; Zhongmin Wan; Shi Li; Liya Rong (Chemical Engineering Journal, 2026)

Effect of ciprofloxacin on performance, antibiotic resistance genes, and microbial communities in mesophilic anaerobic codigestion enriched with Methanosarcina and a recovery strategy after collapse - Bao-Shan Xing; Yong-Ning Feng; Su Li; Liguo Wan; Yi-Fan Wu; Xiaochang C. Wang; Rong Chen; Yu-You Li (Chemical Engineering Journal, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Comprehensive review of constructed wetlands implemented with advanced biotechnologies for carbon-neutral treatment of urban wastewater: Enhanced removal of nitrogen and reduction of greenhouse gas emissions - Feifei Jiao; Xuyihui Chen; Tao Zhang; Chengde Sun; Bin Qi; Shichuang Xu; Xuefei Zhou; Yalei Zhang; Yong Hu; Chao Rong; Dapeng Li; Yu-You Li; et al. (Bioresource Technology, 2026)

Performance stability and recovery strategy of pre-denitrification coupled partial nitritation/anammox-hydroxyapatite processes for enhanced organic matter, nitrogen and phosphorus removal from swine manure digestate - Yunzhi Qian; Shilong He; Fuqiang Chen; Junhao Shen; Chao Rong; Yan Guo; Yu Qin; Yu-You Li (Bioresource Technology, 2026)

Environmental impacts and optimization strategies for integrating carbon capture and anammox-based processes in municipal wastewater treatment under uncertain influent parameters - Rui Zhou; Ying Zhu; Qian Li; Rong Chen; Yu-You Li (Bioresource Technology, 2026)

Investigating the Therapeutic Efficacy of Quality-Controlled, miR-146a-5p-Enriched Small Extracellular Vesicles Derived From MSCs Against Idiopathic Pulmonary Fibrosis - Xin Wang; Lingjiao Meng; Qiuhong Wang; Ruixue Rong; Yu Zhang; Xiaohui Zhao; Chen Liang; Huizhen Guo; Li Deng; Zengqi Tan; Feng Guan; Yi Tan (Stem Cell Reviews and Reports, 2026)
Small extracellular vesicles derived from umbilical cord mesenchymal stem cells (UC-sEvs) may be used for the treatment of idiopathic pulmonary fibrosis (IPF) because of their ability to control inflammation and inhibit fibrosis. However, the lack of clarity regarding the treatment mechanism of IPF and the corresponding quality standards limit the clinical application of these small extracellular vesicles. Here, we established a good manufacturing practice (GMP) grade process for isolating UC-sEvs, and RNA-seq was performed to screen for potential therapeutic cargo in the product to confirm the therapeutic effect of nebulized UC-sEv agents against IPF. Functionally, UC-sEvs inhibited the pulmonary inflammatory response by regulating macrophage function, thereby suppressing the bleomycin toxicity-induced progression of fibrosis. Mechanistically, miR-146a-5p enrichment in UC-sEvs may be involved in alleviating bleomycin-induced IPF by targeting TRAF6/IRAK1 to negatively regulate inflammation. The proposed quality control strategy ensures the stability of the product across three batches, with RNA-seq analysis revealing highly similar miRNA expression profiles. The feasibility of using miR-146a-5p as a key therapeutic molecule has been validated. Finally, on the basis of the results of pharmacodynamics and key therapeutic molecule studies, we provided a detailed quality control standard for IPF therapy by nebulizing UC-sEv. These findings help understand how sEvs impact IPF and the possible consequences of their therapeutic usage and offer a quality standard reference. Graphical Abstract

Anti-cancer effects of Psoralea corylifolia: insights into cancer hallmarks - Pin-Rong Chen; Tz-Syuan Su; Kun-Che Chang; Chien-Chih Chiu; Shu-Pin Huang; Hsin-Chih Yeh; Shu-Chi Wang; Chia-Yang Li (Phytochemistry Reviews, 2026)

miR‑16‑5p Protects RGCs Against Retinal Ischemia–Reperfusion Injury by Modulating Astrocyte-Mediated Neuroinflammation Through the Wip1/NF-κB Signaling Axis - Wen Hu; Wenjing He; Guangyi Huang; Yuchen Zhou; Yue Li; Shuya Tao; Daizai Lei; Fen Tang; Ningning Tang; Li Jiang; Qiangqiang Lan; Hui Huang; et al. (Molecular Neurobiology, 2026)

Nitrification-driven nitrogen mineralization in drylands: regulation by human activity intensity and soil microclimate - Rong Yang; Kai Sun; Shiyang Chen; Wenzhi Zhao; Shujun Song; Xiaojun Li (Journal of Soils and Sediments, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

Mutations in the clpS Gene of Riemerella anatipestifer Affect Stress Response and Bacterial Virulence - Liu Yufu; Liu Jiayi; Liao Ruixin; Rong Fang; Deng Yuanwen; Long Tao; Li Ladi; Cheng Xueyi; Li Sainan; Ouyang Zhengliang; Liu Wenhua; Chen Ruiai (Current Microbiology, 2026)

Quantitative microbial element cycling reveals distinct functional characteristics associated with soil carbon and nitrogen cycling in clear-cut black locust plantations in winter - Kun Li; Yu Chen; Xiangcongcong Kong; Zhixin Rong; Jiaxin Liu; Ruiqiang Ni; Huimei Tian; Jiangbao Xia; Chuanrong Li; Qi Yao; Weixing Shen (Applied Soil Ecology, 2026)

SREBP2 confers ferroptosis resistance by targeting GPX4 in colorectal cancer - Huage Zhong; Ruiqi Chen; Tianyu Chen; Min Lin; Siqi Wen; Man Zhang; Dejun Liu; Junfeng Yu; Jinchi Chen; Bei Yi; Rong Liang; Wei Jiang; et al. (Apoptosis, 2026)

Integrated Analysis of Midgut Transcriptome and Microbiome Reveals That Manganese‐Induced Dysbiosis Drives Metabolic Disruption and Developmental Toxicity in Bombyx mori - Lei Xin; Yazhen Chen; Delong Guan; Lida Huang; Yiwei Lv; Wantao Rong; Xiaodong Li (Environmental Microbiology, 2026)
Manganese (Mn) contamination poses a significant environmental threat, yet the mechanisms underlying its toxicity remain poorly characterised. Here, we used an integrative multi‐omics approach to elucidate how dietary Mn disrupts the gut‐microbiome axis in the silkworm, Bombyx mori . High‐dose Mn exposure triggered severe, dose‐dependent growth retardation, reducing larval weight by 55.1%. This was concurrent with profound gut microbiome dysbiosis, evidenced by reduced bacterial diversity, community homogenisation and a sharp decline in beneficial genera such as Delftia , alongside the complete elimination of key commensals like Bifidobacterium . Host midgut transcriptomics revealed 1255 differentially expressed genes, with significant upregulation of detoxification and stress pathways and marked suppression of genes involved in nutrient metabolism. Critically, integrative analysis demonstrated a strong correlation between microbiome disruption and host metabolic gene expression, suggesting that Mn toxicity operates by disrupting the gut microbiome‐host metabolic axis. Our findings provide crucial mechanistic insights into heavy metal ecotoxicology and highlight the vulnerability of beneficial insect‐microbe symbioses to environmental contamination, with important implications for sustainable agriculture in metal‐polluted regions.